2010 10th IEEE-RAS International Conference on Humanoid Robots 2010
DOI: 10.1109/ichr.2010.5686290
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting sensorimotor stochasticity for learning control of variable impedance actuators

Abstract: Abstract-Novel anthropomorphic robotic systems increasingly employ variable impedance actuation in order to achieve robustness to uncertainty, superior agility and efficiency that are hallmarks of biological systems. Controlling and modulating impedance profiles such that it is optimally tuned to the controlled plant is crucial to realise these benefits. In this work, we propose a methodology to generate optimal control commands for variable impedance actuators under a prescribed tradeoff of task accuracy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…8). While full details about this actuator can be found in [9], here we briefly discuss the salient features. Inspired by human antagonistic muscles, the Edinburgh SEA uses two motors, connected to a pair of springs to adjust equilibrium position and stiffness (and therefore torque) around the joint.…”
Section: A Impedance Modulation On a Single Jointmentioning
confidence: 99%
See 2 more Smart Citations
“…8). While full details about this actuator can be found in [9], here we briefly discuss the salient features. Inspired by human antagonistic muscles, the Edinburgh SEA uses two motors, connected to a pair of springs to adjust equilibrium position and stiffness (and therefore torque) around the joint.…”
Section: A Impedance Modulation On a Single Jointmentioning
confidence: 99%
“…8(b)), and s 1 and s 2 their respective lengths. Note that, there is a non-linear relationship between the latter and the commanded servomotor positions (see [9] for details). Finally, we represent the state of the joint as e x = (q,q) ∈ R 2 , i.e., the instantaneous joint angle and velocity.…”
Section: A Impedance Modulation On a Single Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…It can easily be shown that for co-contraction to change stiffness, non-linear springs must be used, and so most designs for antagonistic variable stiffness focus on creating a suitable non-linear spring (e.g. [18] [11] [19]) or arranging linear springs in such a way as to create non-linearity [20].…”
Section: ) Antagonisticmentioning
confidence: 99%
“…For example, optimal control approaches have been shown to be highly effective in exploiting the elastic properties of variable stiffness actuators in explosive tasks such as throwing and hitting [4], [7] as well as in periodic tasks [8], [9], [10]. In addition, stochastic optimal control with model adaptation has also been exploited in order to cope with model uncertainty and perturbations [11], [12], [13]. This is also consistent with observations regarding the way in which humans adapt their impedance under similar conditions [14].…”
Section: Introductionmentioning
confidence: 99%